An Overview of the Epidemiologic, Diagnostic and Treatment Approaches of COVID-19: What do We Know? - Hanieh Beyrampour-Basmenj; Morteza Milani; Abbas Ebrahimi-Kalan; Ziyad Ben Taleb; Kenneth D Ward; Ghader Dargahi Abbasabad; Zeynab Aliyari-serej; Mohammad Ebrahimi Kalan (Frontiers Media S.A., 2021)
Background: In late December 2019, a new infectious respiratory disease (COVID-19) was reported in a number of patients with a history of exposure to the Huanan seafood market in China. The World Health Organization officially announced the COVID-19 pandemic on March 11, 2020. Here, we provided an overview of the epidemiologic, diagnostic and treatment approaches associated with COVID-19.Methods: We reviewed the publications indexed in major biomedical databases by December 20, 2020 or earlier (updated on May 16, 2021). Search keywords included a combination of: COVID-19, Coronavirus disease 2019, SARS-CoV-2, Epidemiology, Prevention, Diagnosis, Vaccine, and Treatment. We also used available information about COVID-19 from valid sources such as WHO.Results and Conclusion: At the time of writing this review, while most of the countries authorized COVID-19 vaccines for emergency use starting December 8, 2020, there is no a definite cure for it. This review synthesizes current knowledge of virology, epidemiology, clinical symptoms, diagnostic approaches, common treatment strategies, novel potential therapeutic options for control and prevention of COVID-19 infection, available vaccines, public health and clinical implications.